The Influence of Supportive Leadership on Teacher Performance Mediated by OCB and Moderated by Cultural Quotient - Muhammad Nuzul Qadri; Andi M Budihard; Haerul Efendi; Kusman Paluala; Muh. Nur (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study aims to examine the impact of Supportive Leadership and Self-Awareness on Teacher Performance, with Organizational Citizenship Behavior (OCB) as a mediating factor. The main focus is to understand the contribution of leadership and self-awareness in improving teacher performance, as well as explore the role of Cultural Quotient as a moderation of supportive leadership towards organizational citizenship behavior and self-awareness of organizational citizenship behavior. This study uses the Partial Least Squares (PLS) method to analyze the relationship between Supportive Leadership, Self-Awareness, OCB, and Teacher Performance. Data was collected from 211 teachers through a structured questionnaire. PLS was selected to analyze complex relationships and assess the direct and indirect effects of these variables.  The results showed that Supportive Leadership and Self-Awareness had a positive influence on OCB, which in turn improved Teacher Performance. Although Supportive Leadership does not have a direct impact on Teacher Performance, its influence is seen through the increase in OCB. Self-awareness has a direct and indirect positive effect on teacher performance. Cultural Quotient strengthens the influence of Supportive Leadership on OCB. This study concludes that supportive leadership and increased self-awareness are important strategies to improve teacher performance.